2004
DOI: 10.1111/j.1365-2265.2004.02180.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled, prospective study of neuropsychological outcomes post parathyroidectomy in primary hyperparathyroid patients

Abstract: This controlled, prospective study demonstrates no significant improvement in neuropsychological indices using objective, validated psychometric tools in an unselected cohort of PHPT patients. No relationship was found between serum calcium level and the degree of neuropsychological deficit. More studies are needed to assess whether the effect of parathyroidectomy is beneficial and sustainable in PHPT patients with neuropsychological symptoms alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
2
36
1
1
Order By: Relevance
“…Similarly, our longer follow-up showed a decline from both earlier measurements to 6-months' follow-up and therefore we conclude that depressive symptoms normalize over time. Depressed mood is one of the clinically relevant neuropsychiatric symptoms in pHPT, while the influence of calcium on depressive symptoms remains unclear (29,49 (27), who showed a good correlation between the well-established SF-36 and the original English PAS, we were able to show a good correlation for both German versions. Our data emphasize that its administration before and immediately after PTx yields reliable insights into specific changes and that longterm follow-up might not be required as the data did not subsequently change.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Similarly, our longer follow-up showed a decline from both earlier measurements to 6-months' follow-up and therefore we conclude that depressive symptoms normalize over time. Depressed mood is one of the clinically relevant neuropsychiatric symptoms in pHPT, while the influence of calcium on depressive symptoms remains unclear (29,49 (27), who showed a good correlation between the well-established SF-36 and the original English PAS, we were able to show a good correlation for both German versions. Our data emphasize that its administration before and immediately after PTx yields reliable insights into specific changes and that longterm follow-up might not be required as the data did not subsequently change.…”
Section: Discussionsupporting
confidence: 50%
“…However, other studies found no evidence of a positive change in depression scales when comparing PTx patients with patients who underwent orthopedic surgery (29). Concerning asymptomatic pHPT patients, some randomized control studies found moderate positive effects of operation vs medical care on quality of life (30, 31) while others did not (32).…”
Section: Introductionmentioning
confidence: 93%
“…Wilheim et al 2004 observed that both depression and quality of life improved in a similar proportion of patients. However, Chiang (Chiang et al .,2005), did not find significant differences in neuropsychological performance between patients undergoing parathyroidectomy and the controls. On the basis of significant improvement in depressive symptoms and quality of life in patients with mild hypercalcemia, parathyroidectomy has been suggested in the management of asymptomatic hyperparathyroidism (Wilheim et al, 2004).…”
Section: Hyperparathyroidismmentioning
confidence: 92%
“…los estudios sobre los efectos de la paratiroidectomía en la función cognitiva son controvertidos. Algunos estudios muestran mejoría de estos síntomas y mejor calidad de vida [15][16][17] .…”
Section: Figura 1 Test Del Reloj Previo a Cirugía (Izquierda) Y 2 Meunclassified